The Effect of Warming on Visual Response Time in Dominant and Non-Dominant Lower and Upper Extremities - Nurtekin Erkmen; Yağmur Kocaoğlu; Ahmet Kaan Aslan; Yasemin Bayraktar; Abdullah Arguz (Türk Spor ve Egzersiz Dergisi)
The aim of this study was to investigate the effect of warm-up activity on the visual response time of the dominant and non-dominant hand and foot in basketball players. A total of 13 male basketball athletes with an age of 14.38 ± .506 years, height 180.15 ± 8.07 cm, body weight 66.54 ± 13.73 and sports experience 4.69 ± 13.73 years were voluntarily included in the study. Visual response time of the dominant and non-dominant hand and foot were measured before and after the warm-up protocol. The warm-up protocol consisted of a 20-minute warm-up activity including basketball-specific movements and 5-minute stretching movements. Visual response time of the athletes were measured with the Blazepod system. There was no significant difference in the group main effect and time x group interaction of the athletes' hand visual response times after warm-up (F=2.403; p>0.05; F=0.170; p>0.05). There was a statistically significant difference in the time effect (F=22.943; p